FREQUENCY OF BETA THALASSEMIA MAJOR AMONG CHILDREN WITH IRON DEFICIENCY ANEMIA IN PESHAWAR - Safiullah Jan, Nayab; Safiullah Jan, Zahish; Taj Niazi, Humaira; Zameer, Huda; Ain, Qurratul; Humayun, Sidra (Khyber Journal of Medical Sciences, 2022)
Objective: To determine the frequency of beta thalassemia major among children presenting with iron deficiency anemia. Materials and Methods: In this Cross-sectional study, 200 patients were included. The study was conducted between April-October 2020. All patients were subjected to detailed history and clinical examination. 10cc of venous blood was obtained from all patients and was sent to hospital laboratory. Mean + SD was calculated for age, hemoglobin and Ferritin levels. Beta thalassemia major was stratified among age and gender to see the effect modifications using chi square test (p value < 0.05). Results: Mean age was 6 ± 3.39 years. 56% children were male, and 44% children were female. Moreover 5% children suffering from iron deficiency anemia had beta thalassemia major, and 95% children didn’t have beta thalassemia major. Conclusion: Our study concludes that the frequency of beta thalassemia major was 5% among children presenting with iron deficiency anemia.